Functional groups to modify g-C3N4 for improved photocatalytic activity of hydrogen evolution from water splitting - Yu, Fan; Wang, Laichun; Xing, Qiuju; Wang, Dengke; Jiang, Xunheng; Li, Guangchao; Zheng, Anmin; Ai, Fanrong; Zou, Jian-Ping (Chinese chemical letters, 2020)
A new strategy was proposed to improve photocatalytic Hydrogen evolution of g-C3N4via modification of functional groups of NCH. [Display omitted] Rational modification by functional groups was regarded as one of efficient methods to improve the photocatalytic performance of graphitic carbon nitride (g-C3N4). Herein, g-C3N4 with yellow (Y-GCN) and brown (C-GCN) were prepared by using the fresh urea and the urea kept for five years, respectively, for the first time. Experimental results show that the H2 production rate of the C-GCN is 39.06 μmol/h, which is about 5 times of the Y-GCN. Meantime, in terms of apparent quantum efficiency (AQE) at 420 nm, C-GCN has a value of 6.3% and nearly 7.3 times higher than that of Y-GCN (0.86%). The results of XRD, IR, DRS, and NMR show, different from Y-GCN, a new kind of functional group of NCH was firstly in-situ introduced into the C-GCN, resulting in good visible light absorption, and then markedly improving the photocatalytic performance. DFT calculation also confirms the effect of the NCH group band structure of g-C3N4. Furthermore, XPS results demonstrate that the existence of NCH groups in C-GCN results in tight interaction between C-GCN and Pt nanoparticles, and then improves the charge separation and photocatalytic performance. The present work demonstrates a good example of “defect engineering” to modify the intrinsic molecular structure of g-C3N4 and provides a new avenue to enhance the photocatalytic activity of g-C3N4via facile and environmental-friendly method.